You are here:

Question
Could you show me how this is done. I've been having some trouble understanding the subtracting and adding of these types.
calculate: 2^(5/2)-2^(3/2)

Hi Angelo,
Basically, X^a - X^b = X^b . [X^(a-b) - 1]
2^(5/2) - 2^(3/2) = 2^(3/2) . [2^(5/2 - 3/2) - 1]
= 2^(3/2) . (2^1 - 1)
= 2^(3/2) . (2 - 1)
= 2^(3/2)

Notice that 2^(5/2) is twice 2^(3/2) i.e
2^(5/2) = 2 . [2^(3/2)]

On another hand, 2^3 is the square of 2^(3/2) i.e
2^3 = [2^(3/2)]^2
since
(X^a)^b = X^(ab)

Regards
Questioner's Rating
 Rating(1-10) Knowledgeability = 10 Clarity of Response = 10 Politeness = 10 Comment thanks for the explanation -- 10's across the board.

Volunteer

#### Ahmed Salami

##### Expertise

I can provide good answers to questions dealing in almost all of mathematics especially from A`Level downwards. I can as well help a good deal in Physics with most emphasis directed towards mechanics.

##### Experience

Aspiring theoretical physicist. I have been doing maths and physics all my life.

Education/Credentials
I teach mathematics and engineering physics.